Bridging the Gap Between Philanthropy and Reputation: A Qualitative Study of Social Infrastructure, Inequality, and Corporate Culture - Trinitaria Marlis Putri (Asian Journal of Muslim Philanthropy and Citizen Engagement, 2025)
This study examines corporate giving as a strategy in building reputation through philanthropy, focusing on how companies can leverage philanthropic activities to enhance their image and relationships with the community. Corporate giving has long been an integral part of Corporate Social Responsibility (CSR) policies, serving not only to provide social benefits but also to strengthen the company’s position in the market. The approach used in this research is qualitative with a literature study, analyzing relevant literature regarding the relationship between philanthropy and corporate reputation. The findings indicate that companies that integrate philanthropic activities into their organizational culture tend to gain trust and loyalty from consumers, improve relationships with stakeholders, and strengthen long-term reputation. Furthermore, strategically conducted philanthropy can enhance a company’s competitiveness in an increasingly competitive market. However, this study also points out limitations concerning the context used, suggesting that further research with a broader sample is necessary to test these findings across various sectors and countries. In conclusion, corporate giving implemented with the right approach can serve as a tool to strengthen a company’s reputation and contribute to business sustainability